The Influence of Halal Labels, Religiosity, and Producer Attitudes on Halal Certification Compliance: A Study on Micro, Small, and Medium Enterprises (MSMEs) in Lumajang Regency - Dhiasti Eka Wulandari (Department of Islamic Economics, Postgraduate Program, UIN Kiai Haji Achmad Siddiq, Indonesia, 2024)
This study aims to analyze and test the influence of Halal Label, Religiosity, and Producer Attitudes on Halal Certification Compliance. The formulation of the problem presented in this study is, namely, whether there is an influence between Halal Label (X1), Religiosity (X2), and Producer Attitude (X3) on Halal Certification Compliance (Y). The data collection technique uses a questionnaire, distributed to MSME producers in Lumajang Regency. The questionnaire was tested using validity and reliability tests. Then the data were analyzed using descriptive statistical tests, classical assumption tests, Multiple Linear Regression analysis tests. The results of the analysis show that the Halal Label variable has a positive and significant effect on Halal Certification Compliance with a significance value of 0.105. Religiosity has an influence on halal certification compliance. This is proven by the results of SPSS 22.0 calculations. Where the significance value produced is 0.092, because the significance value is 0.05 (0.092<0.05,. Producer Attitude influences halal certification compliance. This is proven by the results of SPSS 22.0 calculations.. Producer Attitude variable (X3). The t-count value is 0.538 with a significance of 0.592. The results of the f test can be seen, Halal Label, Religiosity, and Producer Attitude have a significant effect on halal certification. Because the calculated F is greater than the F table (1.796>2.31) with a significance value of 0.153<0.05. Then H3 is accepted and Ho is rejected